Designing Shopping Centers: The Position of Social Interactions - Rahimi, Alireza; Khazaei, Farhad (Journal of History Culture and Art Research, 2018)
Shopping centers are regarded as the intermittent buildings in which a number of commercial activities work hand in hand to establish a general rule and order in order to improve their common economy. Since shopping centers are normally among those that are created with the collaboration of a number of groups, therefore, planning for them is natural. Reaching a part of the basic organized and functional knowledge to respond to new needs of the commercial centers based on the studies that were done by the theorists of environmental psychology, which is limited to the subject of social interactions, different scales and types of interactions are debated, some of which can be utilized in designing new urban shopping centers with regard to the social and cultural conditions of the city of Tehran. Using them in designing the skeletal sections of the spaces of the shopping centers is possible through the introduction of the main criteria of the creation of interactions. This study investigates these phenomena by implementing a qualitative methodology and a field study.